Selective Determination of Acidic Drugs in Water Samples Using Online Solid Phase Extraction Liquid Chromatography with Alginate Incorporated Multi-Walled Carbon Nanotubes as Extraction Sorbent - Nurzaimah Zaini @ Othman; Nor Suhaila Mohamad Hanapi; Nor’ashikin Saim; Wan Nazihah Wan Ibrahim; Ahmad Lutfi Anis (Indonesian Journal of Chemistry, 2020)
A rapid and effective method is developed for selective determination of five selected acidic drugs (salicylic acid, naproxen, diclofenac, ibuprofen and mefenamic acid) in water samples by using online solid phase extraction (Online-SPE) prior to liquid chromatography diode array detector (LC-DAD) analysis. In this study, Alginate incorporated multi-walled carbon nanotubes (Alg-MWCNT) beads were prepared and utilized as solid phase extraction sorbent. Optimization of online SPE-LC operating parameters such as valve switching time, composition of acetonitrile and buffer pH was conducted using Box-Behnken Design of Response Surface Methodology (RSM) to evaluate the interactive effects of these three variables. Under the optimized conditions (valve switching time: 1.5 min, composition of acetonitrile: MSA, 60:40 and buffer pH: pH 2), the method showed good linearity (1–500 μg L−1) with coefficient of determination (R2) of 0.9971–0.9996 and low limits of detection ≤ 0.018 µg L–1. The method showed high relative recoveries in the range of 75–110% for river water and tap water samples, respectively with RSDs of ≤ 7.8 (n = 3). This method was successfully applied to the determination of acidic drugs in river and tap water samples. In addition, Alg-MWCNT sorbent offered high degree of selectivity and efficiency for online SPE-LC-DAD analysis.